Pasemon dalam Dakwah Digital di YouTube: Sebuah Studi Sosiolinguistik atas Video KH. Anwar Zahid berjudul “Kapolda Jateng Kena Roasting” - Febrian, Rahma; Lestari, Prembayun Miji; Kurnia, Ermi Dyah (Faculty of Languages and Arts, Universitas Negeri Padang, 2026)
Although satire, roasting, and humor in digital media have attracted growing scholarly attention, most existing studies examine these phenomena in entertainment settings, general social media discourse, or broad communication contexts. By contrast, pasemon, a culturally grounded form of Javanese indirect satire, has largely been studied in relation to offline interaction, politeness, and everyday speech. Its role in digitally mediated religious discourse therefore remains underexplored. This study addresses that gap by investigating how pasemon operates in KH. Anwar Zahid’s digital da'wah on YouTube, with specific reference to the video “Kapolda Jateng Kena Roasting” on the Anza channel. Drawing on a sociolinguistic perspective and employing a qualitative descriptive design, the study analyzes utterances containing pasemon transcribed from a 1-hour-44-minute-55-second video. Data were collected through uninvolved observation and note-taking and examined using Miles and Huberman’s interactive model of analysis. The findings demonstrate that pasemon is organized through a three-part discourse structure consisting of an opening, a body, and a closing. Linguistically, it is realized through honorific and double forms of address, satirical humor, hyperbole, and lexical repetition, especially in references to institutional authority and moral-religious imagery. These features allow criticism to be conveyed indirectly while preserving respect, solidarity, and audience acceptability. The study contributes to international sociolinguistic discussions on indirectness, satire, and digital discourse by demonstrating how a local communicative practice is recontextualized and sustained in contemporary online religious communication.